Evaluation of Irrigation Performance at Tertiary Level (A Case Study in Padi Pomahan Irrigation Area Mojokerto East Java) - Mohamad Bagus Ansori; Nastasia Festy Margini; Danayanti Azmi Dewi Nusantara; Nadjadji Anwar (IPTEK Journal of Proceedings Series, 2017)
Padi Pomahan Irrigation Area has a lack of sufficient amount of water at the downstream area in dry season. This problem is caused by some factors such as the exploitation of drinking water, climate change, land use change, and the damage of irrigation channel. The performance of irrigation channel and its facilities compared with the situation nearly 20 years later has never been evaluated and measured due to the limited of the preliminary data. With the area of 4309 hectares managed by two offices (UPT Pugeran and UPT Tangunan), the coordination become more complex to manage the irrigation water in this area. This paper aims to analyze the irrigation performance at tertiary level to measure the performance of six indicators/criterions such as physical infrastructure, plant productivity, personnel organization, operation and maintenance (OM), documentation, and institutional condition of water user associations (P3A / GP3A / IP3A). The results of its performance are expected to obtain the handling priority at the tertiary level in this irrigation system by Indonesian government. The total irrigation performance In Padi Pomahan obtains 61.0%. The result model of AHP (Analytic Hierarchy Process) obtains the result of personnel organization 28.9% (rank 1), plant productivity 20.3% (rank 2),  physical infrastructures 16.8% (rank 3), operation and maintenance (OM 14.2% (rank 4), institutional condition of water user associations ( P3A / GP3A / IP3A) 10.5% (rank 5) and   documentation 9.3% (rank 6). The ARP model obtains CGI value 0.13 and Consistency Ratio (CR) 0.036.